Reluctant Learners Their Identities and Educational Experiences. Occasional Paper / Ruth Wallace. - Wallace, Ruth (Director of SPIL) (Distributed by ERIC Clearinghouse, 2008)
This study explores the relationship between regional people's identities, their experiences of learning, and engagement with learning. Fifteen adult learners describe those experiences of education and the significant impact of their learning identity on their engagement with learning in the long term. The study was based in a regional area of the Northern Territory and includes people from different age groups and backgrounds including Indigenous and non-Indigenous people, long-term residents and migrants from other places. The participants describe their learning identity as it relates to their identity as individuals and members of local, family and global communities. Drawing on interviews with students in regional and rural areas of the Northern Territory, this paper looks at their participation in education and training. The paper suggests that learning strategies which acknowledge rural learners' identities may be successful in engaging regional and remote learners in education and training. [This work has been produced by the author, who received an National Centre for Vocational Education Research (NCVER) New Researcher Award to present their research.]